2012
DOI: 10.1371/journal.pone.0035022
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Expression of Notch1 Increased the Risk of Metastasis in T1 Stage Clear Cell Renal Cell Carcinoma

Abstract: BackgroundAlthough metastasis of clear cell renal cell carcinoma (ccRCC) is basically observed in late stage tumors, T1 stage metastasis of ccRCC can also be found with no definite molecular cause resulting inappropriate selection of surgery method and poor prognosis. Notch signaling is a conserved, widely expressed signal pathway that mediates various cellular processes in normal development and tumorigenesis. This study aims to explore the potential role and mechanism of Notch signaling in the metastasis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 29 publications
4
50
0
Order By: Relevance
“…Our findings are consistent with previous studies demonstrating that elevated Notch1 may contribute to PCa metastases, 16 HCC metastases, 17 and RCC metastases. 18 To our knowledge, this is the first study evaluating and comparing the protein expression levels of Notch1 between human primary and metastatic malignancies from the same tissue origin in multiple cancers simultaneously using IHC staining. Therefore, as a novel approach, our experimental method enables a better comparison of relative expression levels of Notch1 for primary and metastatic malignancies from different organs/ tissues.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our findings are consistent with previous studies demonstrating that elevated Notch1 may contribute to PCa metastases, 16 HCC metastases, 17 and RCC metastases. 18 To our knowledge, this is the first study evaluating and comparing the protein expression levels of Notch1 between human primary and metastatic malignancies from the same tissue origin in multiple cancers simultaneously using IHC staining. Therefore, as a novel approach, our experimental method enables a better comparison of relative expression levels of Notch1 for primary and metastatic malignancies from different organs/ tissues.…”
Section: Discussionmentioning
confidence: 98%
“…17 Furthermore, high-level expression of Notch1 signaling is associated with the metastasis of T1-stage clear-cell renal cell carcinoma (RCC) by stimulating the proliferation and migration of tumor cells. 18 Some literature reports also suggest that Notch signaling may participate in cancer metastasis by modulating EMT, tumor angiogenesis, and anoikis resistance of tumor cells. [19][20][21] In the present study, we used immunohistochemical analysis to compare Notch1 protein expression levels between primary and metastatic malignancies from the same origin in 12 different cancers and demonstrate the elevated expression of Notch1 in some metastatic tumors.…”
Section: Introductionmentioning
confidence: 99%
“…These methods were described previously [36] and detailed elucidated in Supplementary Data. The primers used in the PCR analysis were presented in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, on the basis of the results of multivariate analysis, we constructed a nomogram. Previous studies revealed that Notch signaling pathway played an important role in RCC, [21][22][23][24][25] acute kidney injury, 26 and kidney failure. 27 Sj€ olund et al demonstrated that higher levels of Notch1 expression were detected in ccRCC compared with normal kidney, and inhibition of Notch signaling attenuated the growth of ccRCC cells both in vivo and in vitro.…”
Section: Commentmentioning
confidence: 99%
“…27 Sj€ olund et al demonstrated that higher levels of Notch1 expression were detected in ccRCC compared with normal kidney, and inhibition of Notch signaling attenuated the growth of ccRCC cells both in vivo and in vitro. 21 Ai et al 25 found that high expression of Notch signaling increased the risk of metastasis in T1 stage of ccRCC by stimulating the proliferation and migration of tumor cells. Our previous study demonstrated Notch1 activation can promote RCC growth via PI3K/Akt signaling, 12 and we also found that the expression level of Jagged1, a Notch ligand, was an independent predictor of poor survival in patients with ccRCC.…”
Section: Commentmentioning
confidence: 99%